2019
DOI: 10.3390/s19092082
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Assessment of Solar Radiation by Machine Learning and Deep Neural Network Models Using Data Provided by the COMS MI Geostationary Satellite: A Case Study in South Korea

Abstract: Although data-driven methods including deep neural network (DNN) were introduced, there was not enough assessment about spatial characteristics when using limited ground observation as reference. This work aimed to interpret the feasibility of several machine learning approaches to assess the spatial distribution of solar radiation on Earth based on the Communication, Ocean, and Meteorological Satellite (COMS) Meteorological Imager (MI) geostationary satellite. Four data-driven models were selected (artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 86 publications
1
20
0
Order By: Relevance
“…On the other hand, specialized studies have shown that the proximity towards a forested surface reduces the amount of radiation. This fact is important for people exposed to heat islands specific to the highdensity areas of buildings, also having the role of mitigating the thermal stress in hot summer conditions [34,35]. The integrated analysis of the three analyzed databases clearly illustrate the anthropic intervention regarding the modeling of the relief for the realization of the residential infrastructure by embankments and the realization of terraces for the elevation of the flat surfaces on two levels.…”
Section: Spatial Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, specialized studies have shown that the proximity towards a forested surface reduces the amount of radiation. This fact is important for people exposed to heat islands specific to the highdensity areas of buildings, also having the role of mitigating the thermal stress in hot summer conditions [34,35]. The integrated analysis of the three analyzed databases clearly illustrate the anthropic intervention regarding the modeling of the relief for the realization of the residential infrastructure by embankments and the realization of terraces for the elevation of the flat surfaces on two levels.…”
Section: Spatial Analysismentioning
confidence: 96%
“…On the other hand, specialized studies have shown that the proximity towards a forested surface reduces the amount of radiation. This fact is important for people exposed to heat islands specific to the high-density areas of buildings, also having the role of mitigating the thermal stress in hot summer conditions [34,35].…”
Section: Tourist Infrastructure Accessibilitymentioning
confidence: 99%
“…More recent studies have focused on integrating meteorological satellite images in more complex machine learning models and deep learning networks, as past studies have demonstrated that such methods have the potential to yield superior forecast accuracy, particularly for shorter forecast time horizons [8]. COMS images were used to estimate solar radiation using a deep neural network (DNN) [23,24] and Multi-functional Transport Satellite (MTSAT) images were used to estimate hourly global solar radiation [25]. The MTSAT satellite was replaced by H8 in 2015.…”
Section: Pv Forecast Using Satellite Image Datamentioning
confidence: 99%
“…For this study, COMS bands 1, 2, 4, and 5 and corresponding H8 bands 3, 7, 14, and 15 were used. COMS band 3 (WV) was omitted from this study due to its low significance in comparison to the other bands based on the results of using the random forest algorithm to analyze the relative significance of input variables for solar irradiance estimation [23]. COMS images were downloaded from NMSC as level-1B binary images for the Korea observation area [39], while H8 satellite images were downloaded from Japan Aerospace Exploration Agency (JAXA) using the P-Tree System as level-1 NetCDF data for the Japan observation area [40].…”
Section: Meteorological Satellite Image Datamentioning
confidence: 99%
“…It constructs linear regression in a high-dimensional feature space and is trained based on the principle of structural risk minimization (SRM) [57][58][59][60]. The training dataset of SVR is mapped into the high-dimensional feature space using a nonlinear transformation, which is calculated by kernel functions such as the radial basis function (RBF), Gaussian, and polynomial functions [61,62]. SVR was realized by the software matlab2014a through the fitrsvm function [63].…”
Section: Estimation Of Forest Carbon Densitymentioning
confidence: 99%